Business Models of Islamic Boarding Schools (Pesantren) and Their Sustainability Strategies - Bahrur Rosi; Fauzan Fauzan; M.F Hidayatullah (IFADAH : Jurnal Ekonomi Dan Bisnis Syariah, 2026)
Islamic boarding schools (pesantren), as the oldest Islamic educational institutions in Indonesia, face significant challenges in maintaining institutional sustainability amid modernization and globalization. This study aims to analyze the diverse business models developed by pesantren, identify the sustainability strategies they employ, and examine the Islamic economic principles underpinning their business management practices. The research adopts a qualitative approach using a library research method supported by conceptual analysis of primary and secondary sources. The findings reveal that pesantren business models encompass Islamic boarding school cooperatives (kopontren), agribusiness, retail enterprises, and Baitul Maal wa Tamwil (BMT), all of which are grounded in the principles of amanah (trustworthiness), transparency, and Maqashid al-Shariah. Effective sustainability strategies include business diversification, strengthening Sharia governance, and fostering the development of santripreneurship. A SWOT analysis indicates that pesantren possess strong social capital as a key strength but face challenges related to limited managerial human resources and restricted access to financial capital. This study contributes to the development of value-based business models rooted in Islamic principles that are inclusive, sustainable, and competitive..